2012
DOI: 10.1002/em.21743
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human DNA polymerase delta in the cellular responses to DNA damage

Abstract: The p12 subunit of polymerase delta (Pol d) is degraded in response to DNA damage induced by UV, alkylating agents, oxidative, and replication stresses. This leads to the conversion of the Pol d4 holoenzyme to the heterotrimer, Pol d3. We review studies that establish that Pol d3 formation is an event that could have a major impact on cellular processes in genomic surveillance, DNA replication, and DNA repair. p12 degradation is dependent on the apical ataxia telangiectasia and Rad3 related (ATR) kinase and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 142 publications
4
62
0
Order By: Relevance
“…2 plays a key role in eukaryotic DNA replication and is also involved in gap filling during DNA repair (1,2). Human Pol ␦ is a heterotetramer (Pol ␦4) composed of the p125 (catalytic), p50, p68, and p12 subunits (2)(3)(4)(5).…”
Section: Dna Polymerase ␦ (Pol ␦)mentioning
confidence: 99%
See 3 more Smart Citations
“…2 plays a key role in eukaryotic DNA replication and is also involved in gap filling during DNA repair (1,2). Human Pol ␦ is a heterotetramer (Pol ␦4) composed of the p125 (catalytic), p50, p68, and p12 subunits (2)(3)(4)(5).…”
Section: Dna Polymerase ␦ (Pol ␦)mentioning
confidence: 99%
“…Human Pol ␦ is a heterotetramer (Pol ␦4) composed of the p125 (catalytic), p50, p68, and p12 subunits (2)(3)(4)(5). Evidence in yeast supports a model for a division of labor between Pol ␦ and Pol ⑀ in which Pol ␦ is largely responsible for the synthesis of the lagging strand, and Pol ⑀ is largely responsible for the synthesis of the leading strand (6 -9).…”
Section: Dna Polymerase ␦ (Pol ␦)mentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous studies, we had observed that Pol d is also regulated in the DDR as reviewed by Lee et al (2012). The Pol d smallest subunit p12 is degraded in response to DNA damage that is induced by UV irradiation, alkylating agents, or replication stresses Meng et al 2009;Zhang et al 2007Zhang et al , 2013.…”
Section: Introductionmentioning
confidence: 99%